Palynofacies analysis of surface sediments from the Beagle Channel and its application as modern analogues for Holocene records of Tierra del Fuego, Argentina - Candel, Maria Soledad (2012)
Palynofacies analysis of surface sediments from the Beagle Channel, Tierra del Fuego, Argentina, was carried out to establish modern analogues for comparison with other Holocene marine records in southern Isla Grande de Tierra del Fuego. Our results show the dominance of highly degraded translucent phytoclasts, associated with amorphous organic matter (AOM) and palynomorphs, while opaque phytoclasts are poorly represented. The organic constituents indicate the proximity of the continental source area to marine environments, with distances and/or times of relatively short transport. The predominance of translucent phytoclasts associated with pyrite suggests reducing conditions, probably associated with marginal-marine environments. Among the terrestrial palynomorph group, the predominance of Nothofagus pollen reveals the presence of forests along the channel. The high terrestrial organic matter input to the depositional area are consistent with a marginal-marine environment. The aquatic palynomorphs, mainly dinoflagellate cyst's show assemblages characterised by low species diversity and low concentration values. The dominance of Peridiniales over Gonyaulacales suggests inner neritic environments. Comparison with two fossil sections of Mid–Late Holocene age (Albufera Lanushuaia and Río Ovando) shows similar distribution of the total palynological matter.